DESIGN AND IMPLEMENTATION OF APPLICATION PROGRAMMODULE FOR A POWER STATION SCADA SYSTEM (Journal of Engineering, 2007)
Supervisory Control And Data Acquisition (SCADA) is a commonly used industry term for computer based system allowing system operators to obtain real-time data related to the status of an electric power system over wide geographic area.the designed SCADA system consists ofFive modules and it is designed to work with two layers: Client layer and Data server layer each in a separated PC. The APplication Program (APP) module is one of the SCADA modules that works as an interface between the I/O cards and the other SCADA modules. It collects the data from the I/O cards; through an I/O interface card; and passes it to the Process Data Interchange (PDI) module. And because of the APP module works in a separated PC, it communicate with PDI module using the PC serial port and High-level Data Link Control (HDLC) communication protocol. The designed SCADA modules are programmed as a multithread programs written using Visual C++ programming language. The APP module is built to consist of three threads: one for collecting data, another to perform the communication operation, and the third thread is responsible of controlling all APP operations. The overall SCADA system including the APP module is implemented to supervise the operation of a power station since 1999 and it proves a very fast response time and provides a good real-time reports